NUMERICAL MODELING OF SCALE EFFECTS FOR CIRCULAR CYLINDER IN THE THEORY OF THERMOELASTIC MATERIALS WITH VOIDS - Li, Yulong; Volkov, Alexander V.; Rabinskiy, Lev N.; Shemiakov, Aleksandr O. (Journal of Applied Engineering Science, 2020)
In this paper, numerical modeling of heating for circular cylinders in the frame of the theory of elastic materials with voids (also known as micro-dilatational elasticity) is considered. A numerical solution is build using COMSOL Multiphysics software, where the implementation of the considered theory is realized based on the direct equation-definition approach. Scale effects arising in considered problem are discussed. The maximum stresses increase with an increase of the external radius, but reach the asymptote for sufficiently large values. The classical solution is the particular case of the considered theory, when the coupling number tend to asero, i.e. when the micro-dilatation effects are small and do not affect the material’s stress state. The limiting case in the case of the small value of the coupling number is the classical thermoelasticity solution.
Keywords: Mindlin continuum; elasticity; Saint-Venant problem; kinematical variable; displacement boundary